2023
DOI: 10.31557/apjcp.2023.24.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer in Saudi Arabia: The Way Forward

Abstract: Australia/New Zealand (ASR 36.4 and 27.7 per 100,000 for males and females respectively). The incidence of CRC tends to be low in most regions of Western Africa (ASR 7.0 and 5.1 per 100,000 for males and females respectively), and in South Central Asia (ASR 6.2 and 4.0 per 100,000 for males and females respectively) (Sung et al., 2021). In general, the incidence of CRC in high/very high Human Development Index (HDI) countries is higher (ASR 29.0 and 7.4 per 100,000 for males and females respectively) than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…This region has also witnessed changes in diet and lifestyle patterns, obesity rate in this region is one of the highest in the World 28 . These changes might also have affected not only the incidence of pancreatic cancer but other types of gastrointestinal malignancies, including colorectal cancer 24 . Additionally, one previous study indicated that increasing trends in pancreatic cancer incidence in both sexes were correlated with socioeconomic development 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This region has also witnessed changes in diet and lifestyle patterns, obesity rate in this region is one of the highest in the World 28 . These changes might also have affected not only the incidence of pancreatic cancer but other types of gastrointestinal malignancies, including colorectal cancer 24 . Additionally, one previous study indicated that increasing trends in pancreatic cancer incidence in both sexes were correlated with socioeconomic development 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, our study shows variation in pancreatic cancer incidence between males and females. Sex-related variations are common ndings in the incidence of many cancer types 24 , which may be attributed to a combination of factors that may include sex hormone differences and genetic and epigenetic factors 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is a common malignancy in Saudi Arabia [ 1 , 2 ]. CRC has an age-standardized rate (ASR) of 13.9 per 100,000 in males and an ASR of 11.3 per 100,000 in females in the population of Saudi Arabia [ 3 ]. The mainstay of treatment choice for CRC is surgery [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Saudi Arabia, colorectal cancer tends to present among young, aged individuals, mainly females and is a major burden on healthcare facilities. The mucinous colorectal cancer histological subtype of adenocarcinoma tends to represent approximately 10-15% of all colorectal carcinoma and is characterized by the predominant histological pattern of extracellular mucin [ 3 ].…”
Section: Introductionmentioning
confidence: 99%